The response of East Kalimantan, Indonesia local rice cultivars against iron stress - NURHASANAH NURHASANAH; HELMA SUCI LESTARI; WIDI SUNARYO (Society for Indonesian Biodiversity, 2019)
Nurhasanah, lestari HS, Sunaryo W. 2019. The response of East Kalimantan, Indonesia local rice cultivars against iron stress. Biodiversitas 20: 273-282. Iron (Fe) toxicity is one of the most problematic metal elements in acidic soil. Besides being as an essential micronutrient, an excessive iron can cause mineral and nutrients absorption disorder which leads to disruption of plant metabolism and cell development. Reduction of plant growth and yield will be the further consequences of the excessive soil iron content. This study aimed to evaluate the response of East Kalimantan local rice cultivars and to screen rice genotypes tolerant to iron stress. Twenty-five rice genotypes were used in this study, consisted of twenty-three local rice cultivars of East Kalimantan and two control of iron sensitive (IR64) and tolerant (Mekongga) varieties. Uniform sprouts (3 days old) having 1-1.5 cm root length were used for iron stress experiment. The seedlings were grown in nutrient solution using hydroponic system in an aerobic condition. The seedlings were treated for one week in iron stress condition by adding an extra iron source of 100 and 200 ppm FeSO4.7H2O (pH 4.0). The seedlings grown in the nutrient solution without an extra iron treatment at normal acidity growth condition (pH 5.8) were used as the control. The growth responses were observed from root, shoot, and biomass of the plants. The tolerance index of the plant growth characters was calculated to classify the rice genotypes into tolerant, moderate, and sensitive to iron stress. The results showed that 100 and 200 ppm of FeSO4.7H2O treatments inhibited the root and shoot growth and also reduced the plant biomass. The plant growth reduction was in parallel with the increase of iron concentration. There was a significant differential response of East Kalimantan local rice genotypes to iron stress treatment. Some genotypes showed an extreme reduction of plant growth, whereas several genotypes had an increased growth under stressed situation. In the contrary, the sensitive genotype IR 64 was consistently sensitive based on the tolerance index of the root, shoot, and plant biomass characters. Among all growth parameters, the most selective character for iron toxicity screening was maximal root length character. This character caused the most severe symptoms for most of the genotypes. Two local rice genotypes, Bentian and Bogor Hitam, were consistently tolerant based on the maximal root growth, total root growth, shoot length and plant biomass.